Christianity in the Public Square of Sri Lanka: A Pluri and Inter-Religious Approach - Paul Rohan, J.C. (National Seminary of Sri Lanka, Ampitiya, Kandy, 2024)
In post-modern secular societies like Sri Lanka, the relevance of religious traditions is increasingly questioned. As secularism shapes public policy and social norms, many wonder if faith traditions still have a meaningful role in influencing collective values and ethics. Sri Lanka, known for its rich religious diversity - Buddhism, Hinduism, Islam, and Christianity - has long integrated these traditions into its socio-cultural framework. Despite the rise of secularism, these faith traditions continue to provide moral guidance and spiritual reflection, countering the materialism and individualism often associated with secularization.
Keywords: Public Religion; Secular Constitutionalism; Microcosmic; Syncretic- Homogenous; Proselytism